2012
DOI: 10.1134/s1990793112020108
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics and mechanism of reactions of aliphatic stable nitroxyl radicals with alkyl and peroxide radicals during styrene oxidation

Abstract: A kinetic study (EPR, microvolumometry), quantum chemical analysis (DFT B3LYP/6 31G*), and kinetic simulation of the antioxidant activity of aliphatic stable nitroxyl radicals during styrene oxidation was performed. The key reactions constituting the detailed mechanism of the process were analyzed. It was shown that the inhibiting action of nitroxyl radicals was caused by their reaction not only with alkyl radicals but also with substrate peroxy radicals, which resulted in the regeneration of nitroxyl radicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…Styrene's oxidation can be effectively inhibited by hydroxylamines. This assertion confirms with distinct induction period on oxygen consumption's kinetic curve (typical one represented at Figure 3 (Pliss et al, 2012)). Rate constants of such antioxidants' reactions with peroxide radicals can be determined from inhibited oxidation's rate dependence on time according to the following equation (Loshadkin et al, 2002):…”
Section: Kinetics and Mechanism Of Reactions Of Aliphatic Stable Nitrsupporting
confidence: 69%
See 4 more Smart Citations
“…Styrene's oxidation can be effectively inhibited by hydroxylamines. This assertion confirms with distinct induction period on oxygen consumption's kinetic curve (typical one represented at Figure 3 (Pliss et al, 2012)). Rate constants of such antioxidants' reactions with peroxide radicals can be determined from inhibited oxidation's rate dependence on time according to the following equation (Loshadkin et al, 2002):…”
Section: Kinetics and Mechanism Of Reactions Of Aliphatic Stable Nitrsupporting
confidence: 69%
“…As it has already been mentioned above, reactions of >NO • with peroxide radicals of 1-and 1,1-ethylene substituted monomers were discovered recently (Pliss et al, 2010a(Pliss et al, , 2010b(Pliss et al, , 2012. Authors (Pliss et al, 2010a(Pliss et al, , 2010b on the basis of kinetic data of styrene's and (meth)acrylates' oxidation in presence of piperidine, pyrroline, and imidazoline >NO • suggested that nitroxide radicals inhibit the oxidation process via >NO • reaction with substrate's both alkyl and peroxide radicals, and moreover >NO • regeneration occurs during chain termination process in accordance with reactions:…”
Section: Nitroxide Radicals Reactions With Peroxide Radicals Of 1-andmentioning
confidence: 88%
See 3 more Smart Citations